Takhrij and Syarah Hadith of Agrotechnology: Dates Efficacy Study To Eliminate Toxins - Siti Julaeha; Wahyudin Darmalaksana; Windhy Chandria (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the Prophet's hadith regarding the efficacy of date palms. This research method is qualitative through the approach of takhrij and sharah hadith with agrotechnological analysis. The results and discussion of this research is that the date palm plant is said to have properties and has a large vitamin content. The conclusion of this study is the takhrij and syarah hadith of the Prophet regarding date infused water which has alkaline content, which is said to remove toxins.